Haematological and morphological evaluation of feline whole blood units collected for transfusion purposes. Issue 8 (August 2019) - Spada, Eva; Perego, Roberta; Baggiani, Luciana; Proverbio, Daniela
Objectives: Despite the increasing availability of feline blood collected and stored for transfusion purposes, few studies have been performed on feline blood units. The aim of this prospective in vitro study was to evaluate haematological and morphological changes in feline blood cells in whole blood units between collection and end of storage. Methods: Haematological examination (red blood cells [RBCs], haemoglobin, haematocrit, red cell distribution width, mean cell volume, mean cell haemoglobin concentration, mean cell haemoglobin, white blood cells [WBCs] and platelet [PLT] count) was performed on 40 non-leukoreduced feline whole blood units at the time of collection (day[D]0) and after storage (D35). The blood was collected into citrate–phosphate–dextrose–adenine anticoagulant-preservative solution using an open system in a veterinary blood bank and stored for 35 days at 4 ± 2°C. Twenty of these feline whole blood units were also analysed for blood cell morphology (normal RBCs, macrocytes, echinocytes, spherocytes, schistocytes, lysed RBCs, RBCs with Heinz bodies and recognisable WBC and PLT count). Differences between the two examination times were statistically analysed. Results: There was a statistically significant decrease in WBC and PLT counts after storage at D35 ( P <0.0001 for both). The most significant cellular morphological changes after storage were an increase in echinocyte count ( P = 0.0001), and lysed RBCs ( P <0.0001), and a decrease in normal RBCs ( P <0.0001). Recognisable WBCs – mainly lymphocytes – were present at the end of storage. Conclusions and relevance: This study showed that significant morphological changes occur in RBCs in feline blood units during storage for 35 days. In vivo studies are required to establish if these changes could affect the ability of stored RBCs to circulate and provide adequate oxygen delivery after transfusion.